2019
DOI: 10.1002/chem.201901360
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ligand in the Selective Production of Hydrogen from Formic Acid Catalysed by the Mononuclear Cationic Zinc Complexes [(L)Zn(H)]+ (L=tpy, phen, and bpy)

Abstract: As eries of zinc-based catalysts wase valuated for their efficiency in decomposing formic acid into molecular hydrogen and carbon dioxide in the gas phase using quadrupole ion trap mass spectrometry experiments.T he effectiveness of the catalysts in the series [(L)Zn(H)] + ,w here L = 2,2':6',2''-terpyridine (tpy), 1,10-phenanthroline (phen) or 2,2'-bipyrydine( bpy), wasf ound to dependo nt he ligand used, whicht urned out to be fundamental in tuning the catalytic properties of the zinc complex. Specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Here we show that mononuclear cuprates [(L)Cu(H)] − (where L = H − , O 2 CH − , BH 4 − and CN − ), 12,13 are potent catalysts for the liberation of hydrogen from formic acid. While they follow a similar two-step catalytic cycle (Scheme 2) with similar mechanistic features to other metal hydride complexes previously reported, 15 a key unique feature is that step 2 occurs spontaneously making these catalysts capable of the near thermal activation of formic acid.…”
Section: Introductionsupporting
confidence: 63%
“…Here we show that mononuclear cuprates [(L)Cu(H)] − (where L = H − , O 2 CH − , BH 4 − and CN − ), 12,13 are potent catalysts for the liberation of hydrogen from formic acid. While they follow a similar two-step catalytic cycle (Scheme 2) with similar mechanistic features to other metal hydride complexes previously reported, 15 a key unique feature is that step 2 occurs spontaneously making these catalysts capable of the near thermal activation of formic acid.…”
Section: Introductionsupporting
confidence: 63%
“…17 (mass spectra shown in Figure 7C and 7D for propionic acid; reaction of 4‐Ni with acetic acid is shown in Figure S8B, data for 4‐Pd shown in Figure S8E). This is not surprising considering the fact that numerous metal hydride complex ions have been shown to react with carboxylic acids via acid‐base hydrogen recombination [39,40] true[(phen)M(normalH)]++CH3CO2normalH[(phen)M(normalO2CCH3)]+4pt+4ptnormalH2 …”
Section: Resultsmentioning
confidence: 99%
“…Venugopal and coworkers also found that a 1:1 catalytic mixture of the terminal hydridozinc complex [(Me 6 tren)­ZnH]­[BAr F 4 ] ( 393 ) and BPh 3 promoted the reaction between CO 2 (1.5 atm) and PhSiH 3 to yield the tris­(formate) insertion product PhSi­(OC­(O)­H) 3 at 50 °C in acetonitrile (98% yield, TOF = 29 h –1 ) . Interesting examples of catalytic gas phase formic acid to H 2 and CO 2 decomposition were noted with the cationic zinc hydride complexes [(tpy)­ZnH] + ( 429 ) (tpy = 2,2′:6′,2″-terpyridine), [(bipy)­ZnH] + ( 430 ), and [(phen)­ZnH] + ( 431 ) (phen = 1,10-phenanthroline) . Quite recently, Xu and coworkers noted that the phosphine-substituted NHC complexes [{ArN­(CH) 2 N­(CH 2 CH 2 PPh 2 )­C}­Zn­(μ-H)] 2 (Ar = Mes or Dipp, 432 or 433 ) (Figure ) instigated the reaction between HBpin and CO 2 (10 atm of CO 2 ; C 6 D 6 , 25 °C, TOF = ca.…”
Section: Molecular Hydrides Of Group 12 Metals (Zinc Cadmium and Merc...mentioning
confidence: 99%
“…504 Interesting examples of catalytic gas phase formic acid to H 2 and CO 2 decomposition were noted with the cationic zinc hydride complexes [(tpy)ZnH] + (429) (tpy = 2,2′:6′,2″-terpyridine), [(bipy)ZnH] + (430), and [(phen)-ZnH] + (431) (phen = 1,10-phenanthroline). 543 Quite recently, Xu and coworkers noted that the phosphine-substituted NHC complexes [{ArN(CH) 2 N(CH 2 CH 2 PPh 2 )C}Zn(μ-H)] 2 (Ar = Mes or Dipp, 432 or 433) (Figure 42) instigated the reaction between HBpin and CO 2 (10 atm of CO 2 ; C 6 D 6 , 25 °C, TOF = ca. 3 h −1 ) to give the monohydroborated product HC(O)OBpin; Okuda's complex [IMes•HZn(μ-H) 2 ZnH• IMes] (312) was also explored in this reaction, and gave a slightly lower yield of HC(O)OBpin (31% vs. 68% with 432).…”
Section: Catalysis Mediated By Group 12 Metal Hydride Complexesmentioning
confidence: 99%